2018
DOI: 10.26719/2018.24.5.435
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and associated cardiovascular risk factors among urban slum dwellers in Egypt: a population-based survey

Abstract: Background: The economic deprivation of most slum inhabitants, and the lack of services and facilities may increase their vulnerability to unhealthy lifestyles and cardiovascular diseases. Aims: This study aimed to determine the prevalence of modifiable risk factors for cardiovascular diseases in slum residents in Cairo, Egypt and evaluate their association with hypertension. Methods: A household cluster survey was conducted in Mansheiet Nasser, a large slum area in Cairo. The study included 984 adult particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
14
3
Order By: Relevance
“…In our study, 80.4% of the population have family history of CVDs, which is considered significantly high in comparison with Shaqra city In our research, 34.7% of our participants sometimes consuming fruits and vegetables but 28% consume it rarely. The prevalence of insufficient consuming fruits and vegetables was 62.7% which is a high percentage but still lower than other studies in Nepal (98%) and Egypt (98.4) [17,18] This can also be explained as result of insufficient knowledge on the benefits of fruit and vegetables intake [17]. In our research, 34.7% of our participants were sometimes consuming fruits and vegetables but 28% consume it rarely.…”
Section: Fig 3 the Percentage Of Participants Who Are Consuming Fruits And Vegetablescontrasting
confidence: 75%
See 2 more Smart Citations
“…In our study, 80.4% of the population have family history of CVDs, which is considered significantly high in comparison with Shaqra city In our research, 34.7% of our participants sometimes consuming fruits and vegetables but 28% consume it rarely. The prevalence of insufficient consuming fruits and vegetables was 62.7% which is a high percentage but still lower than other studies in Nepal (98%) and Egypt (98.4) [17,18] This can also be explained as result of insufficient knowledge on the benefits of fruit and vegetables intake [17]. In our research, 34.7% of our participants were sometimes consuming fruits and vegetables but 28% consume it rarely.…”
Section: Fig 3 the Percentage Of Participants Who Are Consuming Fruits And Vegetablescontrasting
confidence: 75%
“…The prevalence of insufficient consuming fruits and vegetables was percentage but still lower n other studies in Nepal (98%) and Egypt (98.4) [17,18] This can also be explained as on the benefits of Smoking puts individuals at higher risk for heart disease and stroke [12]. Our results showed that about 10.3% of our participants are The prevalence of smoking in our study was low in comparison with the prevalence in Gulf countries (13.4% to 37.4%) in males and (0.5% to 20.7%) in females [18], total male and females in Nepal 17.6% [17], in Germany 23.3% [16] and in Bangladesh 40.6% [21]. In our research32.4% were consuming fast food more than one time per week and these results were similar to that reported in the UAE [22].…”
Section: Fig 3 the Percentage Of Participants Who Are Consuming Fruits And Vegetablesmentioning
confidence: 65%
See 1 more Smart Citation
“…Diabetes was defined as fasting capillary blood glucose, 110 mg/ dl or history of antidiabetic treatment [12].…”
Section: Measurementsmentioning
confidence: 99%
“…Low fruit/vegetable consumption of less than 5 portions of fresh and/or cooked fruits/vegetables a day [14]. The Global Physical Activity Questionnaire was used to collect information on physical activity.…”
Section: Operational De Nitionsmentioning
confidence: 99%